Basin hopping simulations for all-atom protein folding - Verma, A; Schug, A; Lee, KH; Wenzel, W (AMER INST PHYSICS, 2006)
We investigate different protocols of the basin hopping technique for de novo protein folding. Using the protein free-energy force field PFF01 we report the reproducible all-atom folding of the 20-amino-acid tryptophan-cage protein [Protein Data Bank (PDB) code: 112y] and of the recently discovered 26-amino-acid potassium channel blocker (PDB code: 1wqc), which exhibits an unusual fold. We find that simulations with increasing cycle length and random starting temperatures perform best in comparison with other parametrizations. The basin hopping technique emerges as a simple but very efficient and robust workhorse for all-atom protein folding. (c) 2006 American Institute of Physics.
Keywords: STOCHASTIC OPTIMIZATION METHODS; PARALLEL TEMPERING METHOD; TRP-CAGE PROTEIN; STRUCTURE PREDICTION; ENERGY LANDSCAPES; GLOBAL OPTIMIZATION; VILLIN HEADPIECE; FORCE-FIELD; MODEL; MINIMIZATION